The Fullness of Free Time : A Theological Account of Leisure and Recreation in the Moral Life - Kelly, Conor M. (Moral traditions series., 2020)
"This book argues that free time-defined as "time free from work, obligation, or any other necessary activity"-is one example of the goodness that can be celebrated as a source of happiness, if only people are primed to see it that way. At the moment, however, there is not a robust sense of the goodness of free time. In the public consciousness, leisure and recreation readily align with binge watching Netflix and laziness. There needs to be both a higher vision for what free time can become, so that people will assess it in light of its potential rather than its nadir, and a clearer sense of the practical path that ordinary people can follow to achieve this end, so that this lofty potential is not relegated to the fate of dismissiveness that befalls all quixotic proposals. These two concerns serve as the rationale for this book, which provides a deeply theological vision for the fullness of free time and then explores how the resources of theological ethics, especially the Catholic understanding of solidarity, can help moral agents transform leisure and recreation for themselves and in their communities in order to make this goodness of free time more apparent and more appealing"--